The experiences of person-centred counsellors working with suicidal clients online through the medium of text. Issue 4 (3rd July 2020) - Harrison, Liz; Wright, Jeannie
ABSTRACT: In this study, we attempt to provide an understanding of the experiences of four UK-based person-centred counsellors working with suicidal clients online using text-based therapies and the impact of their clients' suicidal ideation upon their "way of being". The counsellors were selected purposively; each was working as a person-centred counsellor online, was encountering suicidal ideation in their clients, and was a member of a professional organisation. A narrative approach was taken, using unstructured interviews and a stanza format of representation. We found that participants had developed a way of being online that may be distinct from their in-person practice. Challenges included being more directive, lacking physical presence, lacking confidence in assessing risk and questions about empathic understanding. Working online with risk raises specific challenges for person-centred practitioners in line with what is indicated in the little relevant research currently already available.